Uji Validitas Standar Operasional Prosedur (SOP) Pembelajaran Mikro Reflektif Pada Program Studi Pendidikan Profesi Guru, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Khairun - Roini, Chumidach; Hasan, Said; Limatahu, Iqbal; Suparman, Suparman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to analyze the validity of the draft Standard Operating Procedures (SOP) for reflective micro learning for PPG Pre-service students. The expert validators in this research were 9 language experts and material experts each. The instrument for collecting data is in the form of a questionnaire. The data obtained in the form of a rating scale is then transformed into quantitative data in the form of percentages. The percent data is then categorized for validity. The research results show that the average percentage of SOP validity according to material experts is 94.7% and is categorized as very valid, while according to language experts it is 96.5% and is categorized as very valid.